The protection of technological measures and the management information rights (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
WIPO Treaties on Intellectual Property, European Directive 2001/29/CE and, consequently, our Intellectual Property Law have introduced some regulations related to protection of technological measures and rights management information indigital field. With these rules, legislators try to solve some controversies related tothe use of digital works, like the circumvention of technological measures, and digital management.
Keywords: copyright; Internet; digital management rights.